NIAT MEMBELI DAN ELECTRONIC WORD OF MOUTH DI SITUS JEJARING SOSIAL: PENGUJIAN TERHADAP KUALITAS SITUS WEB, KEAMANAN BERTRANSAKSI, REPUTASI PERSEPSIAN, NORMA SUBYEKTIF DAN KEPERCAYAAN - Camelia L. Numberi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
This research is supported by the emergence of the phenomenon of online communities that become a popular online place for users to search for and gather information about online shopping experiences through online shop or social networking site that aimed to reduce the risk of their transaction. The purpose of this research is to show empirical evidence about the influence of the quality of website, transaction safety, and subjective norm toward purchase intention and electronic word of mouth behavior with mediated of trust and perceived reputation in social networking site. From online survey that conducted we obtain 430 respondents of Facebook users account in Indonesia, and then processed using structural equation modeling (SEM) with the help of the application of Amos 22. Statistical analysis showed that 11 hypothesis that proposed existed four hypothesis unsupported, that is influence of the system quality to perceived reputation, the information quality to trust, the system quality to trust and the perceived reputation to shopping intention. In generally, this research is predicted online consumers behavior in the social networking site with regard to their activities to shopping online, especially about shopping intention and electronic wordof-mouth. Keywords: Social Commerce (S-commerce), Theory of Reasoned Action (TRA), Information Quality, System Quality, Transaction Safety, Perceived Reputation, Trust, Subjective Norms, Shopping Intention, electronic Word-of-Mouth (eWOM), Structural Equation Modeling (SEM).